PENERAPAN MARKERLESS GPS BASED TRACKING DALAM APLIKASI AUGMENTED REALITY UNTUK PENCARIAN LOKASI DI UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Nisa Silaen (2024)
Universitas Pembangunan Nasional (UPN) "Veteran" Jakarta is one of the state universities with a spacious main campus featuring numerous buildings. The campus serves not only as a place for lectures but also for activities such as socialization and workshops. Navigational challenges within the campus arise for faculty, staff, students, especially newcomers, and visitors due to the lack of digital directional signage and limitations of Google Maps features within the campus. Therefore, Augmented Reality (AR) technology is implemented in this research to provide real-world vision information, making the details about building locations at UPN "Veteran" Jakarta Pondok Labu more interactive and informative for users. This technology is integrated into a mobile app utilizing GPS-based tracking and user smartphone coordinates as markers to assist users in locating buildings within the UPN "Veteran" Jakarta Pondok Labu campus using camera-based navigation. The research findings conclude that the implementation of Markerless GPS Based Tracking in the Android-based navigation app at UPN "Veteran" Jakarta achieves a good level of accuracy with an average distance comparison of 0.431 meters. The application proves beneficial in providing interactive navigation information at UPN "Veteran" Jakarta Pondok Labu, with a user satisfaction rate reaching 81.6%. However, it is essential to note that the app's reliability may be influenced by environmental factors and the devices used by users.